Advanced manufacturing (Meridian Education Corporation, 1994)
Advanced manufacturing takes a step beyond the manufacturing technology series, and provides an in-depth view of processes and systems. Quality and increased productivity are emphasized as the viewer sees materials transformed into finished product during the manufacturing process. Computer integrated manufacturing and its continuing influence on manufacturing and the workplace is also discussed.